PERTUMBUHAN DAN KUALITAS Anthurium hookeri PADA BERBAGAI PEMBERIAN BORON - Amalia T Sakya; Muji Rahayu; Retno Wijayanti (Faculty of Agriculture, Universitas Sebelas Maret, 2008)
Title : The Growth and Quality of Anthurium hookeri on Various Boron Application. Anthurium hookeri is one of ornamental plants having high economical and aesthetic value, however they growth slowly. For accelerate their growth can be done by giving accurate nutrient and appropriate concentration. Boron is one of essential nutrient for plant having important role in cell wall and translocation carbohydrate. The aim of this research is to study the effect of applying boron on growth of A. hookeri and to find out the appropriate boron concentration for growth of A. hookeri. The research was arranged based on Split Plot Design with 2 factors and 4 replicates. The main factor was the kind of A. hookeri (green and red) and the sub plot was boron concentration with 4 levels e.i (0; 0,3; 0,6; and 0,9 ppm). The data observation ware analyzed by variance analysis and continued by Duncan Multiple Range Test in level 95 %. The research showed that there was no interaction between the kinds of A. hookeri and boron concentration. Application boron 0,3 ppm increase plant height, number of leaf, and width of leaf red A. hookeri, application boron 0,9 ppm rise plant height, number of leaf, width and quality of the green A. hookeri. Key words: A. hookeri, boron, growth, quality